Developments and Advances in Intelligent Systems and Applications - Rocha, Álvaro; Reis, Luís Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book primarily addresses Intelligent Information Systems (IIS) and the integration of artificial intelligence, intelligent systems and technologies, database technologies and information systems methodologies to create the next generation of information systems. It includes original and state-of-the-art research on theoretical and practical advances in IIS, system architectures, tools and techniques, as well as "success stories" in intelligent information systems. Intended as an interdisciplinary forum in which scientists and professionals could share their research results and report on new developments and advances in intelligent information systems, technologies and related areas - as well as their applications - , it offers a valuable resource for researchers and practitioners alike.
Advanced Classification of Remote Sensing High Resolution Imagery -- An Application for the Management of Natural Resources -- Analyzing the Impact of Strategic Performance Management Systems and Role Ambiguity on Performance: A Qualitative Approach -- Advanced Radial Approach to Resource Location Problems -- Verbal Decision Analysis Applied to the Prioritization of Influencing Factors in Distributed Software Development -- Agile Documentation Tool Concept -- Pervasive Business Intelligence: A Key Success Factor for Business -- Annotated Documents and Expanded CIDOC-CRM Ontology in the Automatic Construction of a Virtual Museum.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence